A Study on the Training and Development Programs for Improving Business Operations in the Field of Tourism and Hotel Sector Under Kerala Cooperative Tourism Sector - B, Muhammed Anas.; Kumar, Anil; V, Sini. (NPRC Journal of Multidisciplinary Research, 2025)
The tourism and hospitality industry in Kerala, India, has experienced significant growth in recent years, largely driven by the contributions of cooperative societies. However, the lack of adequate training and development programs has hindered these cooperatives’ ability to deliver high-quality services and remain competitive. This research aims to investigate the importance of training and development in improving the performance of tourism and hospitality businesses within the Kerala Cooperative Tourism Sector. Utilizing a mixed-methods approach, the study combines quantitative surveys with qualitative interviews. A total of 150 employees and 30 managers from various tourism cooperatives in Kerala participated in the survey to share their perspectives on current training practices, skill gaps, and the impact of training on job performance. Additionally, semi-structured interviews were conducted with 15 industry experts and cooperative leaders to gain deeper insights into the challenges and opportunities related to training and development in the sector. The results reveal a significant positive relationship between the availability of training and employee performance, job satisfaction, and customer satisfaction. Nonetheless, the findings also highlight the shortcomings of existing training programs within the Kerala Cooperative Tourism Sector, as many employees indicated a lack of adequate training opportunities and a misalignment between training content and job requirements.